Assessment of von Willebrand disease and pregnancy outcomes at regional Australian hospitals. (3rd February 2021) - Wilson, Emily; Hanna, Fayez; Hyppa, Annemarie; Orlowski, Ella; Dawar, Hizb U.; Sanga, Zar; Dennis, Amanda; Pavlov, Toly; Khalafallah, Alhossain A.
Abstract: Background: von Willebrand disease (vWD) is a heterogeneous hereditary bleeding disorder and is associated with risk of primary postpartum haemorrhage (PPH). Design and Methods: An observational study at a tertiary referral centre in Australia of 16 women with 23 deliveries with a median age of 27.5 years (range, 21‐39; IQR = 9). Median gestational age at delivery was 39 weeks (range, 35‐41; IQR = 1.1). Results: All cases had type 1 vWD, apart from one case with type 2. Patients were managed in combined obstetrics and haematology clinics. PPH occurred in ten deliveries (44%). Intravenous desmopressin was administered in 6 cases, and IV human vWF was administered in 4 cases. Two cases with mild vWD had received oral tranexamic acid. The median Apgar score at 1 and 5 min was 9 (IQR = 1.0), while the median Apgar score at 10 min was 10.0 (IQR = 0.0). One case required transfusion of blood products postdelivery. There were no other significant complications observed. Conclusions: vWD was associated with a high incidence of primary PPH. Individualised treatment to restore haemostasis, according to the severity of the disease, could achieve as possible, normal haemostasis with favourable outcomes for both mothers and their infants. Further studies to confirm our findings are warranted.